The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/ijmm.2018.3375
|View full text |Cite
|
Sign up to set email alerts
|

Chemical conversion of human lung fibroblasts into neuronal cells

Abstract: It has been previously reported that human embryonic fibroblasts and mouse embryonic fibroblasts can be converted into neuronal cells using chemical agents, along with forced expression specific transcriptional factors. However, the materials required for reprogramming in these approaches presents major technical difficulties and safety concerns. The current study investigated whether a cocktail of small molecules can convert human lung fibroblast cells into neurons. The small molecules valproic acid, CHIR9902… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
(27 reference statements)
1
24
0
Order By: Relevance
“…Indeed, the correlation analysis showed that hepatic H19 mRNA levels were positively correlated with hepatic TGFB1 mRNA and ACTA2, suggesting that H19 mRNA levels could be used to monitor LF progression in BA patients. Similar to the findings in mouse CLI models, the current study showed that H19 levels were markedly increased in serum exosomes isolated from BA patients compared to those in controls. Given that exosomal and hepatic H19 levels are associated with LF in BA patients, serum exosomal H19 levels may be utilized as a useful marker for monitoring LF progression of BA patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, the correlation analysis showed that hepatic H19 mRNA levels were positively correlated with hepatic TGFB1 mRNA and ACTA2, suggesting that H19 mRNA levels could be used to monitor LF progression in BA patients. Similar to the findings in mouse CLI models, the current study showed that H19 levels were markedly increased in serum exosomes isolated from BA patients compared to those in controls. Given that exosomal and hepatic H19 levels are associated with LF in BA patients, serum exosomal H19 levels may be utilized as a useful marker for monitoring LF progression of BA patients.…”
Section: Discussionsupporting
confidence: 89%
“…H19 is highly expressed in fetal liver, but repressed significantly after birth. Intriguingly, it has been reported that H19 is up‐regulated in human liver diseases and CLI animal models, including CCl 4 ‐induced liver injury, bile duct ligation (BDL)‐induced cholestatic injury, and the multidrug resistance 2 knockout ( Mdr2 –/– ) mouse model, implicating its important role in disease progression of CLI. Our recent studies indicate that hepatic H19 level is correlated with severity of cholestatic injury in Mdr2 –/– mice .…”
mentioning
confidence: 99%
“…LncRNA H19 (both hepatic and serum exosomal long noncoding RNA H19) is an imprinted and maternally expressed gene that is conserved between humans and mice and is involved in the regulation of cell proliferation and differentiation [95,96]. A previous study found that H19 is upregulated in CLI animal models and human liver diseases [92,97,98]. H19 plays an important role in the process of liver fibrosis, with inhibition and promotion mediated by different targets.…”
Section: Both Inhibition and Promotion Of Liver Fibrosis By Lncrnamentioning
confidence: 99%
“…As is a master profibrogenic cytokine, TGF-β controls liver physiology and pathology during the initial process of liver injury-inflammation-fibrosis [92,96,97]. TGF-β influences the different biological processes of liver fibrogenesis, including the circadian rhythm, epigenetics, reactive oxygen species generation, metabolism, senescence, EMT, and endothelial to mesenchymal transition [97]. To date, it has been found that lncRNAs cooperate with the TGF-β signalling pathway to regulate HSC activation and hepatic fibrosis.…”
Section: Signalling Pathways Involved In Liver Fibrosismentioning
confidence: 99%
“…At the same time, Pei's work revealed that human fibroblasts were able to transdifferentiate into neurons by a different chemical cocktail (VPA, CHIR99021, RepSox, Forskolin, SP600125, Gö6983, and Y-27632) [ 40 ]. It was also reported that human lung fibroblasts could be converted into neurons using a similar small molecule combination, including VPA, CHIR99021, DMH1, RepSox, Forskolin, Y-27632, and SP600125 [ 41 ].…”
Section: Transdifferentiation In Vitromentioning
confidence: 99%